Genome-wide association-, replication-, and neuroimaging study implicates HOMER1 in the etiology of major depression - Rietschel, Marcella; Mattheisen, Manuel; Frank, Josef; Treutlein, Jens; Degenhardt, Franziska; Breuer, René; Steffens, Michael; Mier, Daniela; Esslinger, Christine; Walter, Henrik; Kirsch, Peter; Erk, Susanne; et al. (Biological psychiatry, 2010)
Background - Genome-wide association studies are a powerful tool for unravelling the genetic background of complex disorders such as major depression. - Methods - We conducted a genome-wide association study of 604 patients with major depression and 1364 population based control subjects. The top hundred findings were followed up in a replication sample of 409 patients and 541 control subjects. - Results - Two SNPs showed nominally significant association in both the genome-wide association study and the replication samples: 1) rs9943849 (pcombined = 3.24E-6) located upstream of the carboxypeptidase M (CPM) gene and 2) rs7713917 (pcombined = 1.48E-6), located in a putative regulatory region of HOMER1. Further evidence for HOMER1 was obtained through gene-wide analysis while conditioning on the genotypes of rs7713917 (pcombined = 4.12E-3). Homer1 knockout mice display behavioral traits that are paradigmatic of depression, and transcriptional variants of Homer1 result in the dysregulation of cortical-limbic circuitry. This is consistent with the findings of our subsequent human imaging genetics study, which revealed that variation in single nucleotide polymorphism rs7713917 had a significant influence on prefrontal activity during executive cognition and anticipation of reward. - Conclusion - Our findings, combined with evidence from preclinical and animal studies, suggest that HOMER1 plays a role in the etiology of major depression and that the genetic variation affects depression via the dysregulation of cognitive and motivational processes.
Gesehen am 24.05.2023